Status of Gibraltar – The Dispute over the Sovereignty after Brexit - Jikia, Mariam; Jincharadze, Ketevan (European Scientific Journal, ESJ, 2022)
Brexit is one of the main issues in EU modern history, which should be dealt with very carefully and with less losses. Brexit caused many political and legal debates regarding different issues, including the Status of Gibraltar, which is affected with the referendum results in 2016. The main factors that defined the final position of Gibraltarians regarding Brexit were geographical and economical factors. Gibraltar is surrounded by water and the only land border neighbor is Spain (which in turn the member of EU). The main factors of economic wellbeing of population are defined by the imported products, services, and labor forces from Spain. Besides the economic factors, Brexit opened the debates on Gibraltar’s Sovereignty, that is the main subject for discussion Between UK and SPAIN more than 300 years. This is the best opportunity given to Spain for offering the joint Sovereignty Model and for strengthening position over Gibraltar. The article offers a historical review of Gibraltar’s Status over the centuries, discusses the main interests of UK and Spain over mentioned territory, offers the main pros and cons of joint sovereignty model and in final part baased on given facts and analysis presents conclusion regarding given issue.